2020
DOI: 10.2196/17345
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Safety Planning With Text Messaging Support for Adolescents at Elevated Suicide Risk: Development and Acceptability Study

Abstract: Background Suicide is the second leading cause of death among adolescents. A critical need exists for developing promising interventions for adolescents after psychiatric hospitalization who are at a high risk of experiencing repeated suicidal behaviors and related crises. The high-risk period following psychiatric hospitalization calls for cost-effective and scalable continuity of care approaches to support adolescents’ transition from inpatient care. Text messages have been used to improve a wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…Nine studies reported that the intervention had been co-designed with adolescents. Texting frequency ranged from several times per day for one depression-focused study [ 56 ] to once every two weeks or month for another depression-focused study [ 54 ]. Most frequently, interventions were delivered in less than 12 weeks, and adolescents received 1-3 messages per week over that time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies reported that the intervention had been co-designed with adolescents. Texting frequency ranged from several times per day for one depression-focused study [ 56 ] to once every two weeks or month for another depression-focused study [ 54 ]. Most frequently, interventions were delivered in less than 12 weeks, and adolescents received 1-3 messages per week over that time.…”
Section: Resultsmentioning
confidence: 99%
“…Text messages across all studies were typically designed to convey empathy and encouragement (eg, “Stop… Breathe… And think about how you got through difficult times before. You got this!” [ 56 ]) and to support coping. The content and authenticity of the messages were cited by adolescent respondents as key elements of their engagement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TextM are perceived as an acceptable, feasible, and supportive tool during the transition period after discharge for an attempted suicide [ 12 , 38 ]. A mobile (smartphone) app used for data collection in one study showed reliability ( r = 0.84) when compared with paper-based PHQ-9 scores [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that MI‐SP, booster calls, and Texts can be feasibly delivered and are acceptable among suicidal adolescent inpatients and their parents (Czyz, Arango, Healy, King, & Walton, 2020; Czyz, King, & Biermann, 2019). Here, extending this prior work, the current nonrestricted pilot SMART included all three components and was conducted to begin obtaining the needed empirical basis for constructing an AI for suicidal youth transitioning from inpatient hospitalization.…”
Section: Introductionmentioning
confidence: 99%